Attention-Deficit / Hyperactivity Disorder and Impulsiveness in Group of patients with Addictive Problems / Behaviors - Muhammad Sheraz Afzal Malik, Ata Ullah, Abid Aftab, Syed Shah Khalid, Munsif Ali, Sar Sikandar Ali Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: The current study aimed to examine Attention-Deficit/Hyperactivity Disorder (ADHD) and impulsiveness among patients with addictive problems or behaviors admitted to the Combined Military Hospital (CMH), Lahore. Methodology: A correlational research design was employed. The sample comprised 90 male patients aged 17 to 55 years, selected through purposive sampling. Inclusion criteria required participants to be over 16, admitted to CMH Lahore, and able to read and understand English. Data were collected using a demographic information sheet, the Attention-Deficit Hyperactivity Disorder (ADHD) scale, and the Barratt Impulsiveness Scale (BIS-11). Statistical analysis was performed using SPSS. Descriptive statistics summarized the data, and Pearson Product-Moment Correlation was applied to examine the relationship between ADHD and impulsiveness. Results: The analysis revealed a significant positive correlation between ADHD and overall impulsiveness (r = .63, p < .01). Additionally, ADHD was positively correlated with all three subscales of impulsiveness: attentional (r = .58), motor (r = .45), and non-planning (r = .49). These findings suggest that individuals with higher ADHD symptoms demonstrate greater impulsivity, which may contribute to the development or maintenance of addictive behaviors. Conclusion: The study supports a significant relationship between ADHD and impulsiveness in individuals with substance use issues. These findings highlight the need for early diagnosis and targeted intervention for ADHD to potentially reduce the risk of substance abuse. Addressing impulsivity in ADHD patients should be integrated into treatment strategies for addiction. Keywords: ADHD, impulsiveness, addiction, BIS-11, substance use disorder, CMH Lahore, comorbidity, behavioral health.